Optimization Model for Compressive Strength of Sandcrete Blocks Using Cassava Peel Ash (CPA) Blended Cement Mortar as Binder - Amartey, Y. D.; Taku, J. K.; Sada, B. H. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
This research work applies Scheffe’s second degree simplex theory to formulate a regression model for the optimization of the compressive strength of sandcrete blocks using cassava peel ash (CPA) blended Portland cement (OPC) as binder material for different mix ratios as multivariate functions with the proportions of the sandcrete block ingredients serving as variables. The experimental values of the compressive strength were obtained by performing destructive strength tests on the blocks after curing for 28 days, with a binder-aggregate ratio of 1:8 and water binder ratio ranging from 0.45 to 0.60, the OPC being replaced with CPA at 0 – 30% for the respective water-binder ratios. The optimization model from the Scheffe’s mixture method for a (4, 2) factor space was found to be y= f(x) = 1.95x1 (2x1-1) + 1.84x2 (2x2-1) +1.81x3 (2x3-1) +1.79x4 (2x4-1) + 6.08x1x2 + 5.72 x1x3 + 1.89 x1x4 + 7.28 x2x3 + 1.80 x2x4 + 7.16 x3x4. The model was tested using the student t- test at 95% accuracy and found to be accurate. Thus, the model can be used to predict any desired compressive strength value for CPA-OPC blended sandcrete blocks given any water-cement ratio between 0.45 and 6.0 and vice versa. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 2, 2017, page:1-14